Economic Effects of Public Investment Activity in Rural Municipalities of Eastern Poland - Czudec, Adam; Zajqc, Dariusz (Economy of Regions, 2021)
For several years, the development of regions of Eastern Poland has been supported with funds from the European Union (EU) special programme entitled «Eastern Poland». Its goal is to stimulate the economic and social development of this part of Poland, which is one of the least developed regions in the EU. These funds are aimed at reducing development disproportions between Eastern Poland and other regions. Therefore, the question about the effects of applying financial support from public funds of these regions is justified. Our research attempts not only to find an answer to this question, but also to fill the research gap explaining the role of some factors in the reduction of regional disparities in rural areas. The paper aims to identify the factors and effects of public investment activity in rural municipalities in Eastern Poland against all rural municipalities in the country. The research hypothesis assumes that there is a positive relation between the level of municipal investment activity and the share of the municipalities’ tax revenue in the overall budget revenue, and that the level of municipal investment activity depends on geographical location of rural areas. The research covered all rural municipalities in five regions of Eastern Poland, while data have been obtained from Central Statistical Office in Poland for the period 2004-2017. A percentage share of investment spending of rural municipalities in the overall budget expenditure was used as a measure of investment activity. The study used a comparative analysis method, descriptive statistics (mean, coefficient of variation), as well as one-factor analysis of variance and linear correlation. The research has shown that investment activity in rural municipalities in Eastern Poland during the analysed period was slightly lower than in the country as a whole, with remarkable differentiation among particular municipalities. There is no single factor defining the investment capacities of local authorities, however, relatively big differences in the receipt of EU funds by rural municipalities in Eastern Poland. The findings show that the proximity to highly developed regions did not energise the economic growth of rural municipalities in Eastern Poland to the same extent as the proximity to larger cities. The research results can be used by public sector institutions in rural development programmes, including measures to improve the effectiveness of the financial investments from public funds to increase the quality of life of rural inhabitants.